Modelling the coordination environment in α‐ketoglutarate dependent oxygenases – a comparative study on the effect of N‐ vs. O‐ligation. Issue 6 (2nd February 2022) - Warm, Katrin; Kass, Dustin; Haumann, Michael; Dau, Holger; Ray, Kallol
Abstract: In various non‐heme iron oxygenases the Fe(II) center is coordinated by 2 N and 1 O atoms of the 2‐His‐2‐carboxylate facial triad; however, most artificial model complexes bear only N‐based ligands. In an effort to closely mimic the coordination environment in α‐ketoglutarate dependent oxygenases, we have now employed the Me2 tacnO ligand (4, 7‐dimethyl‐1‐oxa‐4, 7‐diazacyclononane) in the synthesis of the complexes [(Me2 tacnO)FeCl2 ]2 (1‐NNO ), [(Me2 tacnO)FeCl3 ] (1 b‐NNO ) and [(Me2 tacnO)Fe(BF)Cl] (2‐NNO ; BF=benzoylformate). The weaker donation of the O atom in the ligand was found to result in stronger binding of the ligand in trans ‐position to the O‐atom of the ancillary ligand as compared to the corresponding complexes involving the Me3 tacn (1, 4, 7‐trimethyl‐1, 4, 7‐triazacyclononane) ligand. Furthermore, by stopped‐flow techniques we could detect an intermediate (3‐NNO ) in the reaction of 2‐NNO with O2 . The spectroscopic features of 3‐NNO agree with the involvement of an Fe(IV)‐oxo intermediate and hence this study represents the first detection of such an intermediate in the O2 activation of artificial α‐ketoglutarate Fe(II) complexes. Abstract :